Underutilized crops for diverse, resilient and healthy agri-food systems: a systematic review of sub-Saharan Africa - Ndlovu, Mendy; Scheelbeek, Pauline; Ngidi, Mjabuliseni; Mabhaudhi, Tafadzwanashe (Frontiers in Sustainable Food Systems, 2024)
Sub-Saharan Africa (SSA) faces increasing water scarcity, food and nutrition insecurity, poverty and inequality under climate change. Under these circumstances, promoting locally adapted and nutrient-dense crops is touted as a plausible climate adaptation strategy. We reviewed the utility of neglected and underutilized crop species (NUS) as a climate change adaptation strategy to diversify local food systems and diets and improve nutritional health and environmental outcomes in SSA. We conducted a systematic literature review using Web of Science and Scopus research databases. Of the 1,545 studies retrieved, 75 were included following a multi-level screening process on Covidence guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The review consolidates fragmented knowledge on the application of NUS in different contexts. Despite growing interest, NUS remain gendered and stigmatized crops, marginalized and fragmented in research, development, and marketing efforts and lack explicit support from policy and decision-makers. Despite rhetoric purporting to support them, there is a worrying rise in policies and regulations that inadvertently hinder the development of these crops and reinforce dependence on a narrow basket of crops for food and nutrition security, undermining food sovereignty. Some NUS have received increasing recognition for their potential in the past decade. However, this is neither universal nor systematic, which makes scaling up necessary but challenging. Consequently, progress in mainstreaming NUS in local food systems continues to lag. Despite these challenges, NUS remain sub-Saharan Africa's better-bet option for diversifying food systems and transitioning them to be equitable, inclusive, resilient and healthy; hence, NUS provide positive outcomes for people and the planet under climate change.